The long-acting phosphodiesterase inhibitor Tadalafil does not influence athletes' V·O2max, aerobic, and anaerobic thresholds in normoxia - Di Luigi, L.; Baldari, C.; Pigozzi, F.; Emerenziani, G. P.; Gallotta, M. C.; Iellamo, F.; Ciminelli, E.; Sgrò, P.; Romanelli, F.; Lenzi, A.; Guidetti, L. (International Journal of Sports Medicine, 2008)
Whereas experimental studies showed that in healthy trained subjects, the phosphodiesterase-5 inhibitor (PDE-5i) sildenafil improves exercise capacity in hypoxia and not in normoxia, no studies on the effects of the long half-life PDE-5i tadalafil exist. In order to evaluate whether tadalafil influences functional parameters and performance during a maximal exercise test in normoxia, we studied 14 healthy male athletes in a double-blind cross-over protocol. Each athlete performed two tests on a cycle ergometer, both after placebo or tadalafil (at therapeutic dose: 20 mg) administration. Oxygen consumption (V·O2), blood lactate, respiratory exchange ratio, rate of perceived exertion, arterial blood pressure (BP), heart frequency (HR) and oxygen pulse (V·O2/HR) were evaluated before exercise, at individual ventilatory and anaerobic thresholds (IVT and IAT), at V·O2max and during recovery. Compared to placebo, a single tadalafil administration significantly reduced systolic BP before and after exercise (p < 0.05), decreased V·O2/HR at IVT (13.3 ± 1.8 vs. 14.5 ± 2.1 mL · beat-1; p = 0.03), but did not modify individual V·O2max, IVT, or IAT. In healthy athletes, 20 mg of tadalafil does not substantially influence physical fitness-related parameters, exercise tolerance, and cardiopulmonary responses to maximal exercise in normoxia; it remains to be verified if higher doses/prolonged use influence health and/or sport performance in field conditions.